1990
DOI: 10.1002/path.1711610206
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the jejunal mucosa in human immunodeficiency virus infection

Abstract: The ultrastructural changes in the jejunal mucosa of 11 male patients, three with clinical AIDS, five with AIDS related complex-progressive generalized lymphadenopathy (ARC-PGL), and three who were only HIV antibody positive, were studied. In the enterocytes, major abnormalities were proliferation of smooth endoplasmic reticulum mitochondrial changes, vacuolization of cells, and fat hold up. In the lamina propria, degeneration of enteric nerve axons and smooth muscle were seen. Microvasculature showed both end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…It is possible that the inflammation and damage to enteric nerves that we observed here with SIV infection results in a similar sequence of events, culminating in the degeneration of enteric nerve fibers, retraction of neuronal processes, and loss of intestinal mucosal innervation, thereby contributing to GI dysfunction and enteropathy with HIV/SIV infection. In support of this hypothesis, a reduction of axonal density in lamina propria has been reported in the jejuna of HIV-infected patients without secondary opportunistic enteropathogen infections (2,15,35). In these studies, asymptomatic HIVinfected individuals had similar levels of axonal damage in the jejunum compared to symptomatic patients, suggesting that ENS damage with HIV infection, similar to what we report here with SIV infection, is an early event in the course of disease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is possible that the inflammation and damage to enteric nerves that we observed here with SIV infection results in a similar sequence of events, culminating in the degeneration of enteric nerve fibers, retraction of neuronal processes, and loss of intestinal mucosal innervation, thereby contributing to GI dysfunction and enteropathy with HIV/SIV infection. In support of this hypothesis, a reduction of axonal density in lamina propria has been reported in the jejuna of HIV-infected patients without secondary opportunistic enteropathogen infections (2,15,35). In these studies, asymptomatic HIVinfected individuals had similar levels of axonal damage in the jejunum compared to symptomatic patients, suggesting that ENS damage with HIV infection, similar to what we report here with SIV infection, is an early event in the course of disease.…”
Section: Discussionsupporting
confidence: 89%
“…Like Parkinson's disease, HIV infection also affects the CNS, causing encephalitis and subcortical dementia in infected individuals (12,36,38). However, little information is known regarding the effects of HIV infection on the ENS with the exception of a few early reports describing reduction in axonal density in the jejunum of some HIV-infected patients (2,15,35). These observations collectively demonstrate the close homology and interconnectedness between the ENS and CNS in their susceptibility and response to infectious and degenerative insults and highlight the potential importance of the ENS in the pathogenesis of GI disorders.…”
mentioning
confidence: 99%
“…During the past decade it has become clear that the intestinal mucosa is a site of vigorous virus replication beginning in the very early stages post-infection, and emerging from this storm of replication is a mucosa with a severely depleted CD4+ T-cell population as well as other notable gastrointestinal (GI) pathologies [1]. HIV-associated histopathology in the GI tract includes collagen deposition [2], degeneration of smooth muscle and enteric autonomic nerve fibers [3-5], and abnormal enterocyte morphologies such as villous blunting, vacuolization, and smooth endoplasmic reticulum changes [5,6]. In addition, HIV-1 and simian immunodeficiency virus (SIV) cause direct damage to intestinal epithelial cells [7,8], and gene expression studies of the GI mucosa have revealed HIV-associated upregulation of genes involved in inflammatory and apoptosis pathways [9].…”
Section: Introductionmentioning
confidence: 99%
“…Oral ganciclovir bioavailability was not altered in bone marrow transplant patients with gastrointestinal graft vs host disease [13]. Diarrhoea in these patients may have been related to specific damages in the gastric and small bowel mucosa that are distinct from those observed during HIV infection, especially during specific HIV‐enteropathy that specifically involves the small intestine [3, 5, 26–28]. Therefore, these previous results, in addition to the present findings, may involve at least two different mechanisms.…”
Section: Discussionmentioning
confidence: 54%